2016
DOI: 10.1093/eurheartj/ehw059
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, resting heart rate, and atrial fibrillation: the Tromsø Study

Abstract: In this prospective cohort study, leisure time physical activity was associated with AF in a J-shaped pattern. Moderate physical activity was associated with a reduced risk of AF, whereas higher activity levels attenuated the benefits of moderate activity. Low RHR was a risk factor for AF. Our results support the hypothesis that moderate and vigorous physical activity may affect AF risk via different pathophysiological mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
124
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(146 citation statements)
references
References 32 publications
16
124
2
4
Order By: Relevance
“…74 For recreational activity, the association appears to be J shaped, that is, moderate physical activity reduces risk of AF development, but the benefits are lost at high activity. 75 In the MESA cohort, no association was found between vigorous physical activity or total intentional exercise and incident AF, but in a subgroup of patients who reported no vigorous activity, total intentional exercise was associated with a lower AF incidence. 76 When organized in the form of exercise program tailored for age and physical ability, as was done in the CARDIO-FIT study (Impact of Cardiorespiratory Fitness on Arrhythmia Recurrence in Obese Individuals With Atrial Fibrillation), patients who achieved higher cardiorespiratory fitness were less likely to develop recurrent AF, although low cardiorespiratory fitness was an independent predictor of AF recurrence (HR, 2.75; 95% CI, 1.61-4.68).…”
Section: Impact Of Physical Activity and Obesitymentioning
confidence: 86%
“…74 For recreational activity, the association appears to be J shaped, that is, moderate physical activity reduces risk of AF development, but the benefits are lost at high activity. 75 In the MESA cohort, no association was found between vigorous physical activity or total intentional exercise and incident AF, but in a subgroup of patients who reported no vigorous activity, total intentional exercise was associated with a lower AF incidence. 76 When organized in the form of exercise program tailored for age and physical ability, as was done in the CARDIO-FIT study (Impact of Cardiorespiratory Fitness on Arrhythmia Recurrence in Obese Individuals With Atrial Fibrillation), patients who achieved higher cardiorespiratory fitness were less likely to develop recurrent AF, although low cardiorespiratory fitness was an independent predictor of AF recurrence (HR, 2.75; 95% CI, 1.61-4.68).…”
Section: Impact Of Physical Activity and Obesitymentioning
confidence: 86%
“…In recent prospective observational cohort and trial populations, exercise training has been associated with positive benefits in patients with AF (3,4,22,23). In a recent 20,000 adult observational cohort study, investigators observed lower all-cause mortality in AF patients who self-reported regular physical activity (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that low RHR is associated with higher incidence of AF development in various populations [2224]. Bohn et al reported that RHR lower than 60 beats/min was associated with increased incidence of AF in 27,064 patients with high cardiovascular risk during a mean follow-up period of 4.7 years [22].…”
Section: Discussionmentioning
confidence: 99%